Anti-TRIM21 antibody is associated with aberrant B-cell function and type I interferon production in systemic lupus erythematosus. (November 2021) - Kunishita, Yosuke; Yoshimi, Ryusuke; Kamiyama, Reikou; Kishimoto, Daiga; Komiya, Takaaki; Sakurai, Natsuki; Sugiyama, Yumiko; Takase-Minegishi, Kaoru; Kirino, Yohei; Nagaoka, Shouhei; Nakajima, Hideaki
Background: TRIM21 is a member of the tripartite motif family proteins and is one of the autoantigens which react with anti-SS-A antibody (Ab) present in sera of patients with systemic lupus erythematosus (SLE) and Sjögren's syndrome. Previous studies have shown that TRIM21 dysfunction promotes aberrant B-cell differentiation and Ab production in SLE, and anti-TRIM21 Ab may be related to the TRIM21 dysfunction in human SLE pathogenesis. Here, we examined the relationship between anti-TRIM21 Ab and clinical and immunological characteristics in SLE patients. Methods: Twenty-seven patients with SLE (23 women and four men) before immunosuppressive therapies, who fulfilled the revised 1997 American College of Rheumatology criteria for SLE, and four healthy controls (3 women and one man) were enrolled in the study. SLE patients were divided into two groups according to the seropositivity for anti-TRIM21 Ab. Serum anti-TRIM21 Ab levels were measured using enzyme-linked immunosorbent assays. The serum levels of cytokines and immunoglobulins were measured by cytometer beads arrays. The expression levels of TRIM21 protein in peripheral mononuclear cells (PBMCs) from SLE patients were evaluated by Western blotting. Results: Sixteen and 9 patients showed seronegativity and seropositivity for anti-TRIM21 Ab, respectively. There were no significant differences in the background parameters, including female ratio, age, disease duration, SLE activity, and laboratory data between the two groups. The serum levels of interferon (IFN)-β were significantly higher in patients with anti-TRIM21 Ab as compared with those without anti-TRIM21 Ab ( P = .043). The levels of IgG1 and IgA were significantly higher in SLE patients with anti-TRIM21 Ab as compared with those without anti-TRIM21 Ab ( P = .0022 and .032, respectively). The PBMCs of patients with anti-TRIM21 Ab showed a significantly lower expression of TRIM21 protein as compared with those of patients without anti-TRIM21 Ab ( P = .014). Conclusions: Anti-TRIM21 Ab seropositivity was related to B-cell abnormalities and type I IFN overproduction in SLE patients. These findings suggest that anti-TRIM21 Ab may have an inhibitory effect on TRIM21 functions and be a novel biomarker for the level of dependence on type I IFN overproduction and B-cell abnormalities.